Assessment of Groundwater Vulnerability to Pollution in the Metro Subwatershed Area Using the GOD Method - Yuliani, Emma; Rubiantoro, Prasetyo; Nelvina, Angie; Anggraeni, Voni (Universitas Wiralodra, 2024)
The assessment of groundwater vulnerability to contamination in the Sub-Watershed (Sub DAS) Metro plays a crucial role in maintaining the sustainability of water resources. As an integral part of a complex river system, Sub DAS Metro faces the risk of groundwater pollution caused by human activities such as agriculture, industry, and domestic. Thus, research was conducted to determine the level of groundwater vulnerability using the GOD method (Groundwater Occurrence, Depth to Water Table, and Aquifer Media). The study identified three vulnerability classes out of the five existing classes, namely very low, low, and moderate. The GOD index indicates very low vulnerability with values ranging from 0.08 to 0.10, low vulnerability ranging from 0.11 to 0.12, and moderate vulnerability with a value of 0.48. Following the vulnerability assessment using the GOD method, mapping was conducted, assigning green for very low vulnerability areas, yellow for low vulnerability, and red for moderate vulnerability. The research findings provide strategic insights for designing effective mitigation and sustainable management of groundwater quality in Sub DAS Metro, playing a crucial role in preserving the sustainability of the groundwater ecosystem in the region